PENGAMBILAN SAMPEL BERDASARKAN PERINGKAT PADA ANALISIS REGRESI LINIER SEDERHANA - Wijayanti, Pritha Sekar; Ispriyanti, Dwi; Wuryandari, Triastuti (Jurnal Gaussian, 2013)
Ranked Set Sampling and Ranked Set Sampling concomitant are more efficient than Simple Random Sampling. This can be determined by calculating the Relative Precision which is a ratio value from the variance of the mean from each sampling technique. From the research of Ranked Set Sampling, obtained ,  and  so Ranked Set Sampling is more efficient than Simple Random Sampling. For the research of Ranked Set Sampling concomitant, obtained ,  and  so Ranked Set Sampling concomitant is more efficient than Simple Random Sampling, and for simple linear regression analysis obtained , , ,  so simple linear regression model of Ranked Set Sampling is more efficient than simple linear regression model of Simple Random Sampling